Annual Report (2011-12) on the Working of State Power Utilities Electricity Departments - Planning Commission (Planning Commission, 2011)
It is difficult to say when exactly the first power plant was built in British India. There are, however, scattered reports available and it is said that in January 1887, Kilburn and Co. secured an electric lighting license as agents of the Indian Electric Company Limited. The Company changed its name to the Calcutta Electric Supply Corporation (CESC) soon afterwards. The first power generating company in Calcutta was started in 1899. There is yet another report which speaks of the first diesel power station established in Delhi in 1905. This was a private plant set up by an Englishman in the name of M/s John Fleming. He was given a license under the provisions of the Indian Electricity Act 1903. This particular company, after getting a license set up a small 2 MW diesel set at Lahori Gate in Old Delhi. Later on, the same company was converted to the Delhi Electric Supply and Traction Company. The first hydro electric station in India was erected at Sivasamudram in Mysore in 1902. This was followed by the hydro-electric station for the Bombay area.
(Power & Energy Division) Planning Commission Government of India